Optimalisasi Pengolahan Data Kependudukan Melalui Program Kalimasada Pada Kelurahan Rungkut Tengah - Mutiara Ratri, Lintang; Korika Swasti, Ika (LPPM Politeknik Piksi Ganesha, 2024)
The Kalimasada program was developed to modernize the population administration system by utilizing information and communication technology. However, the community has not fully understood the use of existing applications. The purpose of this research is to identify the challenges and obstacles in implementing the program and provide recommendations for further improvement. A qualitative approach with data triangulation methods, including direct observation, oral interviews, and documentation, was used to determine the community's response to the program's implementation. The research results indicate that the Kalimasada program successfully reduced data processing time, improved the quality of public services, and strengthened data resilience against cyber security threats. Optimization was carried out through strategic steps, including system integration, the use of centralized databases, the application of advanced data processing algorithms, and human resource training and development. Effective implementation of information and communication technology (ICT) is expected to enhance the accuracy, speed, and security of population data processing